2014
DOI: 10.1126/science.1254237
|View full text |Cite
|
Sign up to set email alerts
|

A complex iron-calcium cofactor catalyzing phosphotransfer chemistry

Abstract: Alkaline phosphatases play a crucial role in phosphate acquisition by microorganisms. To expand our understanding of catalysis by this class of enzymes we have determined the structure of the widely-occurring microbial alkaline phosphatase PhoX. The enzyme contains a complex active site cofactor comprising two antiferromagnetically-coupled Fe 3+ ions, three Ca 2+ ions, and a μ 3 -bridging oxo group. Notably, the main part of the cofactor resembles synthetic oxide-centered triangular metal complexes. Structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 43 publications
3
105
0
Order By: Relevance
“…Additionally, several Vibrio species are able to fix N, a process that has a very high Fe demand (38,39). Dust additions also likely added other limiting nutrients in addition to Fe, especially phosphate, which may help to explain the continued response even at very high levels (16). Finally, although the focus of this work was on Vibrio as a model for dust response, the relative abundance of other taxa (e.g., Pseudoalteromonas and Acinetobacter) also increased significantly with dust events and likely competed with Vibrio for uptake of additional Fe and nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, several Vibrio species are able to fix N, a process that has a very high Fe demand (38,39). Dust additions also likely added other limiting nutrients in addition to Fe, especially phosphate, which may help to explain the continued response even at very high levels (16). Finally, although the focus of this work was on Vibrio as a model for dust response, the relative abundance of other taxa (e.g., Pseudoalteromonas and Acinetobacter) also increased significantly with dust events and likely competed with Vibrio for uptake of additional Fe and nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…This genetic repertoire suggests that Vibrio are effective competitors for Fe in many different environmental niches. The availability of Fe can also control the metabolism of other nutrients such as N and P, and can limit C utilization, effectively setting limits on growth for both open ocean and coastal heterotrophic bacteria (16,33,34). Potential colimitation is especially important in light of the fundamental contribution of heterotrophic bacteria to the cycling of C in marine ecosystems (33,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there have even been reports that the activity of organic phosphorus acquisition may be constrained by zinc availability: recent field studies in the North Atlantic observed stimulation of alkaline phosphatase activity following the addition of zinc (Mahaffey et al, 2014). There are two isoforms of the alkaline phosphatase enzyme, the zinc PhoA and recently characterized iron-calcium PhoX (Duhamel et al, 2010;Shaked et al, 2006;Yong et al, 2014). PhoX was previously thought to be a calciumonly enzyme (Kathuria and Martiny, 2011).…”
Section: Connecting Metal Distributions To Metaproteomic Metalloenzymmentioning
confidence: 99%
“…Furthermore, marine bacteria contain more iron per unit biomass than phytoplankton, and thus, bacterial iron assimilation may constitute another constraint on iron availability to phytoplankton (646). Iron is also a key resource limiting microbial N 2 fixation, phosphate acquisition, and, thus, productivity in the ocean (181,(647)(648)(649). It has been proposed that iron may control productivity in half of the world's oceans (650,651) and may have accounted for onequarter of the decrease in the atmospheric CO 2 concentration during the Earth's historical glacial maxima (652).…”
Section: Cheating: It Happens In the Microbial World Toomentioning
confidence: 99%